Tenofovir and Severe Symptomatic Hypophosphatemia. (May 2019) - Kichloo, Asim; Chugh, Savneek Singh; Gupta, Sanjeev; Panday, Jay; Goldar, Ghazaleh
Tenofovir is a broadly used drug used for the treatment of human immunodeficiency virus (HIV). Although the initial results of the clinical trials supported the renal safety of Tenofovir, clinical use of it has caused a low, albeit a significant, risk of renal damage either in the form of AKI or CKD. The pathophysiology has been linked to the effect of this medication on the proximal tubular cell. Although the exact mechanism is unknown, studies have suggested that Tenofovir accumulates in proximal tubular cells which are rich in mitochondria. It is both filtered in the glomerulus and actively secreted in the tubules for elimination and is excreted unchanged in the urine. Studies have shown an active transportation of 20-30% of this drug into the renal proximal tubule (PCT) cells via the organic anion transporters in the baso-lateral membrane (primarily hOAT1, and OAT3 to a lesser extent) and ultimate excretion of the drug into the tubular lumen via the transporters in the proximal tubular apical membrane MRP4 and MRP2 (multidrug resistance-associated proteins 2 & 4). Subsequently, the mitochondrial injury caused by Tenofovir can lead to the development of Fanconi's syndrome which causes renal tubular acidosis, phosphaturia, aminoaciduria, glucosuria with normoglycemia, and tubular proteinuria. Here we present a case where Tenofovir treatment resulted in severe hypophosphatemia requiring hospitalization for parentral phosphate repletion.